2009
DOI: 10.1097/mpa.0b013e3181a16d28
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Human Telomerase Reverse Transcriptase in Pancreatic Juice as a Biomarker of Pancreatic Malignancy

Abstract: Our results suggested that the assessment of hTERT expression in preoperative pancreatic juice increased the sensitivity and accuracy of diagnosis of PDACs and malignant IPMNs without using special techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 29 publications
(23 reference statements)
0
20
0
1
Order By: Relevance
“…An examination of hTERT expression in pancreatic juice samples (obtained after secretin stimulation)from patients with PC and IPMN revealed that while cytology was 47% sensitive and 57% accurate in distinguishing malignant cells from benign cells, a positive staining for hTERT was nearly 85% sensitive and over 80% accurate in achieving this distinction [142]. Significantly, among the PC cases, hTERT staining correctly identified 17 out of 21 cases that were negative for malignant cells by cytology.…”
Section: Biomarkers In Body Fluidsmentioning
confidence: 99%
“…An examination of hTERT expression in pancreatic juice samples (obtained after secretin stimulation)from patients with PC and IPMN revealed that while cytology was 47% sensitive and 57% accurate in distinguishing malignant cells from benign cells, a positive staining for hTERT was nearly 85% sensitive and over 80% accurate in achieving this distinction [142]. Significantly, among the PC cases, hTERT staining correctly identified 17 out of 21 cases that were negative for malignant cells by cytology.…”
Section: Biomarkers In Body Fluidsmentioning
confidence: 99%
“…An alternative to measuring telomerase activity is to measure the expression of one of its RNA components, TERT, whose expression closely correlates with telomerase activity and can be more readily assayed in clinical samples (30). TERT RNA levels in pancreatic juice samples collected from the pancreatic duct can accurately differentiate benign from malignant pancreatic lesions (3133). Studies have also measured TERT RNA in resected pancreatic cystic neoplasm specimens as a marker of telomerase activity (34).…”
Section: Introductionmentioning
confidence: 99%
“…Exocrine pancreatic secretions, or pancreatic juice, collected from the second part of the duodenum after stimulation with intravenous synthetic human secretin using an upper endoscope 3-5 have been analyzed for molecular markers associated with pancreatic ductal adenocarcinoma (PDAC) 6, 7. Protein and gene expression profiles in the pancreatic juice of patients with PDAC have revealed novel protein markers and indicator genes that might be useful for PDAC diagnosis 8, 9.…”
Section: Introductionmentioning
confidence: 99%